"New beginnings" within a new normal for the four futures. Issue 6 (10th November 2014) - Dator, Jim
Abstract : Purpose: – This paper aims to offer real and explicit reasons for viewing the futures of humanity and Earth as positive, fulfilling and meaningful, if humans view it as such and act to make it so. The paper incorporates the results of several recent research projects and activities that were based on the assumptions of an earlier paper titled, "The Unholy Trinity, Plus One." It argues that the conclusions of the original paper are even more obvious and urgent than they were originally, and that while an "alternative futures" perspective must always be the basis of any statements about or actions toward the futures, the concerns of The Unholy Trinity, Plus One, are now part of a "new normal" that must be incorporated in each of the alternatives. This paper emphasizes that this "new normal" is, and must be prepared for as, a splendid opportunity for humans to start on new adventures; that one episode of human history (based on cheap and abundant energy, a benign environment, effective government and continued economic growth) is over, and a world with different challenges and opportunities for New Beginnings has already opened up. It concludes by offering an example of how the transition might be approached and managed positively and effectively. Design/methodology/approach: – Both papers relied heavily on a combination of trend analysis and emerging issues analysis viewed through the lens of four generic alternative futures for understanding continuing trends and anticipating new, emerging issues, and for then formulating appropriate anticipatory responses to them. Findings: – The fundamental findings reconfirm and deepen the original findings – that it is far too late to prevent or postpone the transformative effects of The Unholy Trinity, Plus One; that one must and can prepare for and welcome them as providing humans now and in the immediate futures with an opportunity for innovation, identity, meaning and vibrant lives. The research and practical experiences and simulations illuminated ways in which these positive futures might be achieved. Research limitations/implications: – It is urgent that humans now turn their attention from either denying the fact of overwhelming change or trying to prop up old economic, governmental and educational systems, and begin to invent new systems that are appropriate for making the transition from the old environment to new ones. Social implications: – At the end of the paper, the authors offer one example of a successful transition, based on the research. It is presented as though humans are in Hawaii in the future, after oil has stopped flowing, along with the imported food, products and tourists upon which humans are now entirely dependent, and Hawaii has once again become entirely self-sufficient and prosperous. Originality/value: – The main focus of the paper, in contrast to most that deal with this issue, is to encourage readers not only to consider the inevitability of rapid and extensive social, environmental, resource and institutional change, but also, by viewing the situation as a positive, welcomed opportunity for innovation and improvement, actually to make it so.